Importance of Roadless Areas for the European Conservation Network - Psaralexi, Maria K.; Votsi, Nefta-Eleftheria P.; Selva, Nuria; Mazaris, Antonios D.; Pantis, John D. (Frontiers in Ecology and Evolution, 2017)
Protected Areas are a main conservation tool to halt biodiversity loss. However, their performance has been often questioned and the need to improve their effectiveness is now more apparent than ever. Here, we propose Roadless Areas as a conservation target to increase the cover and effectiveness of Protected Areas. Roadless Areas represent natural and semi-natural areas of high conservation value that have no or little traffic and provide multiple ecosystem services. Here, we develop a methodological framework to identify Roadless Areas in Europe and assess their spatial properties and conservation status. We examine how the European Union’s conservation network, Natura 2000, would expand if Roadless Areas that are already partially included in Natura 2000 terrestrial sites or are adjacent to them would be added to the existing conservation network. We find that European lands are highly fragmented. Roadless Areas are unevenly distributed, and cover more than 30% of the European Union territory, with large Roadless Areas (≥100 km2) occupying about 18% of that surface. At the national level, there is a large variation in the percentage of overlap between Natura 2000 sites and Roadless Areas, with the Natura 2000 network currently encompassing between 19% and 89% of the Roadless Areas surface, depending on the member state. Our results demonstrate that Roadless Areas adjacent to Natura 2000 sites cover > 65% of the total Natura 2000 surface. As Roadless Areas have limited human access, we suggest integrating Roadless Areas into biodiversity conservation networks as a timely solution to minimize conflicts over expanding Protected Areas in the European Union and to achieve the goals of the European Union’s 2020 Biodiversity Strategy.